2005
DOI: 10.1080/15216540500149904
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Regulation of Intestinal Iron Absorption

Abstract: SummaryThe intestinal absorption of the essential trace element iron and its mobilization from storage sites in the body are controlled by systemic signals that reflect tissue iron requirements. Recent advances have indicated that the liver-derived peptide hepcidin plays a central role in this process by repressing iron release from intestinal enterocytes, macrophages and other body cells. When iron requirements are increased, hepcidin levels decline and more iron enters the plasma. It has been proposed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…HJV indeed plays an essential role in the regulation of hepcidin expression, specifically in the iron-sensing pathway, although through unknown mechanisms [7] . It has been reported that HFE, HJV, TfR2 and HAMP genes are closely related, but the precise underlying mechanism(s) were not revealed [7,22,23] . For many years the signal transduction pathways that regulate systemic iron homeostasis have been unknown.…”
Section: Hemojuvelin and Iron Metabolismmentioning
confidence: 99%
“…HJV indeed plays an essential role in the regulation of hepcidin expression, specifically in the iron-sensing pathway, although through unknown mechanisms [7] . It has been reported that HFE, HJV, TfR2 and HAMP genes are closely related, but the precise underlying mechanism(s) were not revealed [7,22,23] . For many years the signal transduction pathways that regulate systemic iron homeostasis have been unknown.…”
Section: Hemojuvelin and Iron Metabolismmentioning
confidence: 99%
“…Grande quantidade de fatores externos interfere na absorção de ferro, dificultando a compreensão dos mecanismos reguladores da concentração desse metal no organismo (1,3,5,7,8,11,13,14,17,21) . No presente estudo, procurou-se reduzir a influência externa no mecanismo de absorção, através da perfusão de solução salina com ascorbato de ferro II em alça isolada.…”
Section: Discussionunclassified
“…Quando ocorre aumento da necessidade de ferro, a concentração da hepadicina diminui, aumentando a absorção do ferro. A concentração de transferrina atua como regulador da produção de hepadicina (8,21) . A absorção do ferro inorgânico é influenciada por múltiplos fatores.…”
Section: Introductionunclassified
“…When the body is iron-replete, macrophages of the liver, spleen, bone marrow, and reticuloendothelial system can also store iron recovered from the phagocytosis of senescent erythrocytes. Inside the macrophage, iron is released from hemoglobin and can either be stored or released back into the circulation (Steele et al, 2005; Camaschella and Pagani, 2011). Depending on the intracellular iron levels, each cell regulates iron uptake mostly by modulating the expression of TFR1, while the efflux of iron through FPN is regulated systemically under the control of the liver-derived peptide hepcidin (HAMP) (Krause et al, 2000).…”
Section: Body Iron Homeostasismentioning
confidence: 99%